Trust in social actors and attitudes towards genetically modified organisms in Slovenia - Zajc, Jožica (Družboslovne razprave, 2013)
This article tries to fulfil the research gap left by the fact that no study to date has examined how trust in social actors affects attitudes towards genetically modified organisms (GMOs). Therefore, two key hypotheses were posited: a) trust in social actors is a more important factor of attitudes towards GMOs than knowledge about GMOs; and b) trust in certain social actors is a more important factor than trust in other social actors. Telephone survey data of adult Slovenians were used. The analyses show that: a) general trust in social actors has a positive effect on attitudes towards GMOs; b) trust in various social actors has different effects; and c) trust in social actors has a stronger effect on attitudes towards GMOs than knowledge about GMOs.
Keywords: Trust; Zaupanje; Transgenic organisms; Gensko spremenjeni organizmi; Attitudes; Stališča; Social science methodology; Družboslovna metodologija; Multivariate analysis; Multivariatna analiza; Slovenia; Slovenija